The effects of talent management practices towards job satisfaction and performance management among academicians in selected public higher learning institutions - Mohd Kamal Muhsin Mohd Yunus
Problem statement: The Higher Learning Institutions (HLIs) in abroad have implemented Talent Management (TM) for years and they have successfully developed the human capital. Due to this, the Ministry of Higher Education (MOHE) took an initiative to implement TM in Malaysia public HLIs. Therefore, it is important to measure the effect of TM in public HUs especially in the area of Job Satisfaction (JS) and Performance Management (PM) among academicians. Thus, this study is conducted to examine the effects of TM on Job Satisfaction (JS) and Performance Management (PM) in selected public HUs. Methodology: Quantitative and Qualitative methods have been used to conduct this research in selected public HLIs, which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSl) and Universiti Teknologi Mara (UiTM). In quantitative method, descriptive survey has been conducted towards 714 respondents. Meanwhile, in qualitative method, semi-structured interview has been conducted towards the deans. Further, the data collected was analyzed by using IBM Statistical Packages Social Sciences (SPSS) and ATLAS.Ti were used to analyze information obtained from the quantitative and qualitative method. Result: USM showed the highest level of TM practise as compared to UPSI and UiTM. Next, all selected public HLIs have moderate level relationship between TM practices, JS and PM. However, USM scored slightly higher in relationship between TM practices, JS and PM as compared to UPSI and UiTM. Furthermore, the significant difference of TM practices perceived by academician revealed that there were significant differences in the selected public HLIs. In addition, all deans agreed that the challenges in conducting TM practises were coming from all aspect of attracting, recruiting, developing and retaining talent. Conclusion: This research revealed that the effect of TM practices towards JS and PM are still in moderate state. Therefore, the result from this research would be an eye opener to the MOHE and top management of public HLIs to do a check and balance about TM practise in order to have better managerial system in public HLIs as a whole.